USE OF ROTATIONAL FURNACES FOR RECYCLING OF IRON-CONTAINING WASTE - S. L. Rovin (Литьë и металлургия)
The article is devoted to the problem of recycling of disperse iron-containing waste and possibility of application of rotary rocking furnaces (RRF) for solution of this problem. Modeling of processes of heat-mass exchange in rotary furnaces is carried out, original constructions of high-capacity furnaces are developed.